Digital video activities and their influence for the improvement of english teaching-learning process in students of eighth year of basic education at Virginia Reyes González School in Anconcito, Salinas, Santa Elena province year 2014-2015. - Piguave Alfonzo, Yenny Verónica (2015)
The general objective of this research is to propose the application of digital activities through video techniques in order to improve the English teaching and learning process in students of eighth year at Virginia Reyes González School in Anconcito, Salinas as a way to contribute with the integral development of students. It was observed that some teachers do not use technological tools and internet. The Government requires that teachers contribute to digital Education. Some have been trained, but others do not like to change their traditional methods to the new digital age. It is true that today’s society integrates the use of information and communication technologies (ICTs) and it is precisely in education where technological strategies should be implemented facilitating a meaningful and cooperative learning to allow students to consolidate the acquired knowledge, and to let teachers look for new knowledge and digital resources that motivate students and they can learn other language through YouTube videos, an online video repository in which nearly any digital video file can be stored and exhibited free of charge. Here you can find activities and methods to teach. The Role of Teachers is to guide students with current knowledge. In fact YouTube is a valuable tool through which multiple foreign language skills can be taught. Using YouTube both inside and outside the classroom can enhance conversation, listening, and pronunciation skills therefore they are utilized to stimulate lessons, and develop authentic vocabulary. These digital activities are fundamental in the improvement of the independent learning of the students and teachers.